Clinical Study of Hollow Viscous Perforation - Dr. Sreenivasa. P (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Peritonitis due to hallow visceral perforation is commonly encounter edin surgical practice it is defined as inflammation of the serosal membrane that lines the abdominal cavity and the organs contained there in. Peritonitis is often caused by introduction of an infection into the otherwise sterileperitoneal environment through perforation of bowel, Introduction of a chemically irritating material, such as gastricacid from a perforatedulcer. The different modes of presentation of cases may be misleading the diagnosis of its origin. A prospective observation of 50 cases of perforation peritonitis in the Dept. of Surgery in M.N.R Medical college and hospital sangareddy during the period of October 2014 to September 2016 were to be included in the study.